Influence of the COVID-19 pandemic on future mobility to the workplace or study center - Cerro Herrero, David; Prieto Prieto, Josué; Tapia Serrano, Miguel Angel; Vaquero Solis, Mikel; Sánchez Miguel, Pedro Antonio (Revista Transporte y Territorio, 2021)
Urban mobility is a fundamental element of cities and to be able to intervene on it is necessary to know the personal reasons for choosing a method of transportation. The pandemic caused by Covid-19 has brought about great changes in people’s lives. The present study tries to know if these affect the way of moving habitually. For this purpose, a sample of 290 people was available who answered a questionnaire about their situation during the pandemic and their preferences for urban mobility. The results showed that there will be significant changes towards active mobility (walking and cycling) and towards the use of private vehicles and a decrease in the use of public transport (bus and train). Before these changes, cities must implement measures to promote active displacement and prevent the car boom from causing new problems of contamination or saturation of public space.